Dañarse, ambientarse y restituirse en el placer : territorios y representaciones sociales de hombres homosexuales en Medellín, 1970-1990 (Antioquia, Colombia) (2016)
ABSTRACT: This article presents an approach to the forms of social representation of gay men in Medellin since late 1960s to early 1990s, describing images produced on the social stage to play the maverick or banished from regular sexual order character and the processes of self-representation of homosexual subjects in the conquest of a place and an identity in the city from a series of processes of territorial and subjective reinvention.